Shaping the Securities Industry Spatial Pattern by Institutional Arrangements in China: An Analysis Based on Headquarters Location of Securities Companies - Zhang Xuchen; Pan Fenghua (Redai dili)
As a crucial capital intermediary, the securities industry has gradually become an integral part of financial markets and plays a vital role in shaping financial center cities. Although the securities industry of China has a relatively short history of development, its spatial structure has undergone a substantial transformation. Nevertheless, the existing research has yet to thoroughly investigate the spatial evolution of the securities industry, especially in terms of how institutional arrangements impact its spatial organization. This study systematically analyzes the establishment, exit, and headquarters relocation of securities companies across China from 1992 to 2022 and investigates the role of institutional arrangements in shaping the spatial configuration of the securities sector. The main findings reveal three critical insights. (1) The spatial distribution of securities company headquarters in China has evolved from a dispersed to a highly concentrated layout. During the formative years of the industry, most provincial capital cities in China established local securities companies, resulting in a relatively scattered distribution of headquarters across the country. However, as the industry expanded and matured, securities companies in smaller cities gradually relocated or shut down, and new establishments or relocations of securities companies became predominantly concentrated in Beijing, Shanghai, and Shenzhen, causing these three cities to gradually become the central hubs of the industry. (2) Institutional arrangements concentrated on key securities resources in a few selected cities, forming the foundational spatial structure of China's securities industry. From the early days of the industry, central government policies have played a decisive role in shaping the spatial organization of the securities sector. Shanghai and Shenzhen were designated the only cities legally permitted to host stock exchanges, granting them a unique infrastructural advantage that naturally fostered the growth and concentration of the securities industry. Beijing, the location of the China Securities Regulatory Commission, has been pivotal in shaping the spatial structure of the industry. The centralized regulatory and financial infrastructure, combined with preferential policies for key cities, has created a distinct pattern of spatial concentration, with Beijing, Shanghai, and Shenzhen forming the core centers of China's securities industry. (3) Institutional factors consistently influence the spatial dynamics of the securities industry across its developmental stages. From the early government-directed capital deployment to establish local securities companies to state-owned enterprises' involvement in managing high-risk securities companies during industry cleanups, institutional factors have been crucial in shaping the evolution of the industry's spatial distribution. Recently, regulatory interventions for foreign-invested securities firms, including policy-driven decisions regarding the location of their headquarters, have played a significant role in consolidating the industry within major financial hubs. These interventions, including preferential policies, mergers and acquisitions, and support for foreign investments, significantly altered the distribution of securities companies across China. The evolving regulatory landscape, along with China's unique institutional characteristics, has ensured that the country's securities industry remains highly centralized, with significant financial resources concentrated in key cities. This study theoretically addresses the gap in Western-focused perspectives by highlighting how institutional factors shape the spatial structure of China's securities industry. While the clustering of securities firms in financial centers may align with market trends, China's distinctive institutional framework has acted as a powerful force driving the spatial evolution of the industry. Thus, this study provides valuable insights into the dynamic spatial patterns of the financial sector within China's regulatory environment, contributing essential perspectives on the development of financial center cities and deepening our understanding of the mechanisms shaping financial center cities under China's unique institutional conditions.